A Zoom-Based Specification Tool for Corporate User Interface Development - Memmel, Thomas; Geyer, Florian; Rinn, Johannes; Reiterer, Harald (My University, 2008)
We introduce a UI specification tool that interactively integrates interdisciplinary and informal modelling languages with different fidelities of UI prototyping. Our innovative experimental tool, called INSPECTOR, is the first tool that assembles models and design into a UI specification with a zoom-based visualization approach.
Keywords: User Interface Specification; Interdisciplinary Modelling; 004